The evaluation of the caveolin-1 and AT-rich interactive domain 1 alpha expressions in uterine smooth muscle tumors - Duygu Ayaz; Gulden Diniz; Dudu Solakoglu Kahraman; Sevil Sayhan; Melek Uncel; Tugba Karadeniz; Muzaffer Sanci (Wolters Kluwer Medknow Publications, 2016)
Objectives: This retrospective study was designed to evaluate the importance of tissue expressions of caveolin-1 (Cav-1) and AT-rich interactive domain 1 alpha (ARID-1A) which are known as signal regulator and tumor suppressor in differential diagnosis of uterine smooth muscle tumors (SMTs). Materials and Methods: Thirty patients recently diagnosed as uterine SMTs at the Tepecik Training and Research Hospital were identified using pathology databases. Immunohistochemical stains for Cav-1 and ARID-1A were performed. Results: In this series, there were 10 leiomyosarcomas (LMSs), 10 uterine smooth muscle tumors of uncertain malignant potentials (STUMPs), and 10 leiomyomas (LMs). Cav-1 expression located cytoplasmic or perivascular area. Cytoplasmic Cav-1 expression was determined in 5 LMSs and 2 STUMPs while perivascular Cav-1 expression was determined in 9 LMSs and 2 STUMPs. Statistically, it was determined that if the tumor becomes malignant and more invasive, it gains the perivascular Cav-1 expression (P = 0.029). On the other hand, the mean nuclear staining rate for ARID-1A in LMSs (63 ± 23.4%) was higher than both STUMPs (60 ± 18.5%) and LMs (34.5 ± 16.5%). Statistically, it was determined that the expression of ARID-1A was significantly downregulated in LMs when compared with STUMPs and LMSs (P = 0.004). Conclusions: Our findings were demonstrated that perivascular Cav-1 expression was seen to be a marker for malignancy of uterine SMTs. Similarly, we found to link of ARID-1A expression and the aggressiveness of SMTs. Therefore, it may be suggested that Cav-1 and ARID-1A may act as predictive biomarkers in uterine SMTs.